Pengembangan Model Wisata Berbasis PENCILS Analysis dalam Meningkatkan Destinasi Wisata Tematik untuk Mendukung Pembangunan dan Pemerataan Ekonomi di Jawa Timur - Leonard Adrie Manafe; Ririn Andriana; Moh Wahib (Universitas Negeri Surabaya, 2025)
This study aims to analyze the key factors influencing destination performance and sustainability in cultural heritage-based tourism. Specifically, it investigates the impact of community involvement, events, identity media, lobbying, news, publication, and social investment on destination development across three cultural tourism sites in East Java, Indonesia. The research adopts a quantitative approach using Structural Equation Modeling (SEM) with SmartPLS. Data were collected from 90 respondents representing multiple stakeholders, including tourists, local communities, destination managers, and local government representatives from Kampoeng Heritage Kajoetangan Kota Malang. Measurement model validity and reliability were ensured through convergent and discriminant validity, Cronbach’s alpha, and composite reliability tests. The findings reveal that lobbying and news significantly influence destination performance, whereas community involvement, events, identity media, publication, and social investment do not show significant effects. These results highlight the strategic role of advocacy efforts and media coverage in enhancing the visibility and competitiveness of tourism destinations. The study concludes that policy advocacy and media-based communication are more effective in strengthening destination sustainability than community participation or general promotional activities. The findings provide practical implications for destination managers and policymakers to prioritize lobbying and media strategies to improve cultural tourism performance. Theoretically, the study contributes to tourism destination research by addressing gaps in the effectiveness of stakeholder engagement strategies. Future research should expand the sample across broader regions and integrate longitudinal analysis to capture dynamic influences over time.